Identification of absolute geometries of cis and trans molecular isomers by Coulomb Explosion Imaging - Ablikim, Utuq; Bomme, Cédric; Xiong, Hui; Savelyev, Evgeny; Obaid, Razib; Kaderiya, Balram; Augustin, Sven; Schnorr, Kirsten; Dumitriu, Ileana; Osipov, Timur; Bilodeau, René; Kilcoyne, David; et al. (My University, 2016)
An experimental route to identify and separate geometric isomers by means of coincident Coulomb explosion imaging is presented, allowing isomer-resolved photoionization studies on isomerically mixed samples. We demonstrate the technique on cis/trans 1,2-dibromoethene (C2H2Br2). The momentum correlation between the bromine ions in a three-body fragmentation process induced by bromine 3d inner-shell photoionization is used to identify the cis and trans structures of the isomers. The experimentally determined momentum correlations and the isomer-resolved fragment-ion kinetic energies are matched closely by a classical Coulomb explosion model.